Thyroid Surgery under Local Anaesthesia: Study of 30 Cases - Ahmad, Ashfaq; Amin, Mamoon Ibn; Hossain, HS Mubarak; Chawdhury, Muhammad Mukit Osman (Journal of Current and Advance Medical Research, 2018)
Background: Thyroidectomy is usually done under general anaesthesia. Objective: The purpose of the present study was to present our experience and evaluate effectiveness of thyroid surgery under local anaesthesia. Methodology: This is a cross-sectional study carried out in upazila health complex, Boalkhali, Chittagong and 250 bed General Hospital, Chittagong since January 2013 to December 2015. 30 patient underwent thyroidectomy for benign and malignant diseases under local anaesthesia. All patients are adult from 20 to 60 years, examined thoroughly investigated accordingly, euthyroid or made euthyroid, normotensive or made normotensive. Each patient was given Tab. Bromazepam 3mg at night before the day of surgery and repeated in morning on the day of surgery. Half an hour before the surgery patient is given injection Pethidine 1mg/kg I.M, injection Ketorolac 30mg I.V, injection Ranitidine 50mg I.V, injection Ondansetron 8mg I.V, injection Ceftriaxone 1gm I.V. Result: Among 30 patients male 8, female 22. Male-Female ration 1:2.75. Mean age 33.8 years. Mean lesion size 5.95cm. Mean Operation time: 91min. Surgery included hemithyroidectomy 18, subtotal thyroidectomy 8, total thyroidectomy 6. Post operative complication included infection in 1 and haematoma in 1 case. Conclusion: In our study thyroidectomy under local anaesthesia found effective and safe in a setup of limited anaesthesia facilities and safe alternative where general anaesthesia is contraindicated. Journal of Current and Advance Medical Research 2016;3(2):56-59